Cerebral bioenergetic differences measured by phosphorus‐31 magnetic resonance spectroscopy between bipolar disorder and healthy subjects living in two different regions suggesting possible effects of altitude. Issue 9 (3rd July 2019) - Hwang, Jaeuk; DeLisi, Lynn E.; Öngür, Dost; Riley, Colin; Zuo, Chun; Shi, Xianfeng; Sung, Young‐Hoon; Kondo, Douglas; Kim, Tae‐Suk; Villafuerte, Rosemond; Smedberg, Diane; Yurgelun‐Todd, Deborah; et al.
Abstract : Aim: Increased oxidative stress in cerebral mitochondria may follow exposure to the systemic hypobaric hypoxia associated with residing at higher altitudes. Because mitochondrial dysfunction is implicated in bipolar disorder (BD) pathophysiology, this may impact the cerebral bioenergetics in BD. In this study, we evaluated the cerebral bioenergetics of BD and healthy control (HC) subjects at two sites, located at sea level and at moderate altitude. Methods: Forty‐three veterans with BD and 33 HC veterans were recruited in Boston ( n = 22) and Salt Lake City (SLC; n = 54). Levels of phosphocreatine, β nucleoside triphosphate (βNTP), inorganic phosphate, and pH over total phosphate (TP) were measured using phosphorus‐31 magnetic resonance spectroscopy in the following brain regions: anterior cingulate cortex and posterior occipital cortex, as well as bilateral prefrontal and occipitoparietal (OP) white matter (WM). Results: A significant main effect of site was found in βNTP/TP (Boston > SLC) and phosphocreatine/TP (Boston < SLC) in most cortical and WM regions, and inorganic phosphate/TP (Boston < SLC) in OP regions. A main effect analysis of BD diagnosis demonstrated a lower pH in posterior occipital cortex and right OP WM and a lower βNTP/TP in right prefrontal WM in BD subjects, compared to HC subjects. Conclusion: The study showed that there were cerebral bioenergetic differences in both BD and HC veteran participants at two different sites, which may be partly explained by altitude difference. Future studies are needed to replicate these results in order to elucidate the dysfunctional mitochondrial changes that occur in response to hypobaric hypoxia.